An approach to detect web services vague datatype specifications to enhance understandability. (2016) - Hanna, Samer
Web services are important for integrating distributed heterogeneous applications. Web services datatype specifications inside a WSDL interface are difficult to be understood by service requestors and this fact hinders the understandability of web services. A reason for this problem is that web services depend on XML schema-based datatypes and these datatypes are not expressive enough to map many of the web services provider side datatypes written in high level programming languages such as Java and C#. This research investigates the previous problem by analysing the datatype specifications inside WSDLs generated when developing web services by different techniques. Based on this analysis, the paper proposes an approach to detect vague, custom, and similar datatype specifications produced by each of the investigated web services development techniques. When service providers detect such specifications, they can then annotate these specifications to reach for more understandable WSDL interfaces and hence more understandable web services. To demonstrate the usefulness of the proposed approach, a proof of concept tool has been built and this tool proved to be efficient in detecting vague, custom and similar datatype specifications serialised by different web services development techniques.